The Nonlinearity Between The Economic Growth, International Economy And Income Inequality Using Method Of Moments Quantile Regression - Tarchoun, Monaem; Ghraieb, Ikram (Journal of Ecohumanism, 2025)
The relationship between inequality, economic growth, and the international economy is one of the most studied topics and is seen as a major problem to be solved. What is new is that researchers and policymakers have shifted their attention to divisible inequality at levels of its value. In this context, our article contributes to examining the link between inequality and economic growth by taking into account the international economic relations of three panels of countries grouped according to their income levels during the period 1990–2020. The study used a method of moments quantile regression to examine these variables at different levels of inequality. The estimates yielded the following findings: There were that disparities between various quantiles in each of the three panels' countries (HIC, MIC, and LIC) were influenced differently by the international economy, economic growth, and financial development. In order to solve inequality based on financial development, economic growth, or/and international economic variables, policymakers can benefit greatly from our findings, which have a number of implications. Therefore, it is crucial from an economic policy perspective because they offer empirical support for the distributional effects of FDI: Governments can use foreign direct investment (FDI) to improve population wellbeing and reduce inequality.